Prevalence of Dental Anomalies in Orthodontic Patients - P. Černochová; L. Izakovičová Hollá (Czech Dental Chamber, 2013)
Aim: The aim of the present study was to assess the prevalence of dental anomalies and associations among them in Czech orthodontic patients and to verify possible association between the prevalence of dental anomalies and gender. Material and methods: The retrospective study comprised 400 consecutive orthodontic patients, 170 males (aged 15.48 ± 6.26) and 230 females (15.59 ± 6.28). The prevalence of dental anomalies was evaluated on panoramic radiographs, lateral cephalograms and dental casts. Results: It was found that 56.75% of the orthodontic patients had dental anomalies, 27.5% of the patients exhibited at least two dental anomalies. The ectopic eruption and impaction of permanent teeth were detected in 31% of the patients (upper canines - 20.5%, premolars - 3.5%, lower canines - 3%, upper incisors -2.75% and molars (without third molars) - 1.5%). Agenesis was registered in 26.25% of the patients (third molars - 20%, second premolars - 7.75%, upper lateral incisors - 4.5%, lower central incisors - 1.5%, upper canines - 0.75%). Anomalies of the upper lateral incisors were found in 8.25% of the patients. Bilateral prevalence was significantly higher than unilateral. Shape anomalies of the lateral incisor tooth crown were detected in 4.5% of the patients. Statistically significant correlations were found between shape anomalies of upper lateral incisors and ectopic eruption of adjacent canines. The prevalence of supernumerary teeth was 2.75%, taurodontism 2.5%, transposition 1.25%, short root anomaly 3%. Unlike other anomalies, the prevalence of short root anomaly was significantly higher in females. Conclusion: Results of this study support opinions of Hoffmeister and other authors that dental anomalies are determined by genetic predisposition to disturbed development of dentition.